2007
DOI: 10.1002/chem.200600689
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Fluorescence, and Two‐Photon Absorption of a Series of Elongated Rodlike and Banana‐Shaped Quadrupolar Fluorophores: A Comprehensive Study of Structure–Property Relationships

Abstract: An extensive series of push-push and pull-pull derivatives was prepared from the symmetrical functionalization of an ambivalent core with conjugated rods made from arylenevinylene or arylene-ethynylene building blocks, bearing different acceptor or donor endgroups. Their absorption and photoluminescence as well as their two-photon absorption (TPA) properties in the near infrared (NIR) region have been systematically investigated in order to derive structure-property relationships and lay the guidelines for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
204
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 240 publications
(228 citation statements)
references
References 116 publications
14
204
0
10
Order By: Relevance
“…77 . The squarine dye 3 was synthesized from squaric acid and corresponding methylene base, using similar experimental conditions as reported in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…77 . The squarine dye 3 was synthesized from squaric acid and corresponding methylene base, using similar experimental conditions as reported in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…A large body of experimental data is available for many families of quadrupolar systems. [3,33,36,57,58,63,76,78,81,85,86,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] Their nonlinear response is a non-trivial function of terminal donor and acceptor strength, π-conjugated bridge length and type, nature of the conjugated core, torsional disorder, symmetry and topology. [58] In this subsection we exemplify some of these relationships using two different families of quadrupoles to derive general trends in terms of TPA cross sections and peak positions.…”
Section: Quadrupolar Chromophoresmentioning
confidence: 99%
“…Thereby, attention has progressively moved from the well-known push-pull dipolar molecular structures [34,41,[75][76][77][78][79][80][81][82][83][84][85][86][87][88] to quadrupoles [3,33,36,57,58,63,76,78,81,85,86,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] and, more recently, toward complex molecular architectures. Quadrupoles have been found to be more efficient than dipoles in terms of TPA, in particular for multiphoton-based opticallimiting applications.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was found that the ethylene linker ensures improved conjugation between various parts of the molecule leading typically to a stronger bathochromic shift, a larger two-photon absorption cross-section and higher quantum yields. 28,29 In our case however, the comparison of optical properties of dyes 4 and 5 reveals that both their absorption and emission are bathochromically shifted versus those of their analogues bearing the C-C double bond 23 (Table 1). The effect of solvent polarity on the emission intensity is also profound.…”
Section: Photophysical Propertiesmentioning
confidence: 53%